The application of postactivation potentiation to elite sport - Docherty, D.; Hodgson, M. J. (International Journal of Sports Physiology and Performance, 2007)
Recently there has been considerable interest and research into the functional significance of postactivation potentiation (PAP) on sport performance. The interest has evolved around the potential for enhancing acute performance or the long-term training effect, typically in the form of complex training. Complex training usually involves performing a weight-training exercise with high loads before executing a plyometric exercise with similar biomechanical demands. Despite a considerable amount of research in the past 10 years it would seem there is still much research to be done to fully determine whether PAP has a functional role and, if so, how to best exploit it. It is clear from the research that there are many factors that need to be considered when attempting to apply PAP to an athlete. It is possible that a well-conceived sport-specific warm-up might be as or more effective in enhancing acute performance and easier to apply in a practical setting. In addition, despite its current popularity, there has not been 1 study that has effectively examined the efficacy of complex training and whether it has any advantage over other forms of training that combine weight training and plyometrics but not in the same training session.